Apply the Properties of Integer Exponents to generate equivalent expressions to (7^−3)^7⋅ 7^20/6^−2 with only positive exponents, then solve the expression. Provide the answer as an improper fraction.(1 point)

5 answers

To apply the properties of integer exponents, we can first simplify the expression $(7^{-3})^7$ by multiplying the exponents: $(7^{-3})^7 = 7^{-3 \cdot 7} = 7^{-21}$.

Next, we can simplify the expression $7^{20}$ by multiplying the exponents: $7^{20} = 7^{\frac{2}{6} \cdot (-2)} = (7^{1/3})^{-2} = \left(\frac{1}{7^{-1/3}}\right)^2 = \left(\frac{1}{\sqrt[3]{7}}\right)^2 = \left(\frac{1}{\sqrt[3]{7}}\right)^{2\cdot3} = \frac{1}{7^2} = \frac{1}{49}$.

Therefore, the expression $(7^{-3})^7 \cdot 7^{20} \div 6^{-2}$ is equivalent to $7^{-21} \cdot \frac{1}{49} \div 6^{-2}$.

Now, let's simplify the expression using the quotient and power rules of exponents:

$7^{-21} \cdot \frac{1}{49} \div 6^{-2} = \frac{1}{7^{21}} \cdot \frac{1}{49} \div \frac{1}{6^2} = \frac{1}{7^{21}} \cdot \frac{1}{49} \cdot 6^2 = \frac{1}{7^{21}} \cdot \frac{1}{49} \cdot 36 = \frac{1 \cdot 1 \cdot 36}{7^{21} \cdot 49} = \frac{36}{7^{21} \cdot 49}$.

So the answer is $\frac{36}{7^{21} \cdot 49}$.
what?????
I apologize for any confusion. Let's start over.

The expression we are given is $(7^{-3})^7 \cdot 7^{20} \div 6^{-2}$.

Using the property $(a^m)^n = a^{m \cdot n}$, we can simplify $(7^{-3})^7$ as $7^{-3 \cdot 7} = 7^{-21}$.

Using the property $a^m \cdot a^n = a^{m + n}$, we can simplify the expression as $7^{-21} \cdot 7^{20} \div 6^{-2}$.

Applying the property $a^m \div a^n = a^{m - n}$, we can simplify further as $7^{-21} \cdot 7^{20} \cdot 6^2$.

Applying the property $a^{-n} = \frac{1}{a^n}$, we have $\frac{1}{7^{21}} \cdot 7^{20} \cdot 6^2$.

Simplifying $7^{20}$ as $7^{20} = 7^{\frac{3}{3} \cdot 20} = (7^{\frac{1}{3}})^{60} = (7^{1/3})^{60} = (7^{1/3})^{2 \cdot 30} = (7^{1/3})^{2 \cdot 3 \cdot 10} = (7^{1/3})^{6 \cdot 10} = (7^{1/3})^{60} = (\sqrt[3]{7})^{60} = (\sqrt[3]{7})^{3 \cdot 20} = (\sqrt[3]{7})^{20} = \left(\frac{1}{\sqrt[3]{7^{-1}}}\right)^{20} = \left(\frac{1}{\sqrt[3]{7}}\right)^{20} = \left(\frac{1}{\sqrt[3]{7}}\right)^{3 \cdot 6 + 2} = \left(\frac{1}{\sqrt[3]{7}}\right)^{3 \cdot 6} \cdot \left(\frac{1}{\sqrt[3]{7}}\right)^2 = (7^{\frac{1}{3}})^{-6} \cdot (7^{\frac{1}{3}})^{-2} = 7^{-6} \cdot 7^{-2} = \frac{1}{7^6} \cdot \frac{1}{7^2} = \frac{1}{7^6 \cdot 7^2} = \frac{1}{7^8}$.

Therefore, the expression simplifies to $\frac{1}{7^{21}} \cdot \frac{1}{7^8} \cdot 6^2 = \frac{1}{7^{21}} \cdot \frac{1}{7^8} \cdot 36 = \frac{36}{7^{21} \cdot 7^8} = \frac{36}{7^{21+8}} = \frac{36}{7^{29}}$.

So the answer is $\frac{36}{7^{29}}$.

I apologize for any confusion caused by my previous response.
ANSWER MORE CLAR
I apologize for any confusion. Let's go through the steps again in a clearer manner.

The expression we are given is $(7^{-3})^7 \cdot 7^{20} \div 6^{-2}$.

First, let's simplify $(7^{-3})^7$. Using the property $(a^m)^n = a^{m \cdot n}$, we have $(7^{-3})^7 = 7^{-3 \cdot 7} = 7^{-21}$.

Next, let's simplify $7^{20}$.

To do this, we can rewrite $7^{20}$ as $7^{6 \cdot \frac{20}{6}}$, where $\frac{20}{6}$ is the same as $\frac{2}{6} \cdot (-2)$.

Using the property $a^{m/n} = \sqrt[n]{a^m}$, we simplify $\frac{2}{6}$ as $\sqrt[3]{7^2}$.

Therefore, $7^{20} = 7^{6 \cdot \sqrt[3]{7^2}} = (7^6)^{\sqrt[3]{7^2}} = (\sqrt[3]{7^6})^2 = 7^2 = 49$.

Now, let's simplify $6^{-2}$. Using the property $a^{-n} = \frac{1}{a^n}$, we have $6^{-2} = \frac{1}{6^2} = \frac{1}{36}$.

Putting it all together, our expression becomes $7^{-21} \cdot 49 \div \frac{1}{36}$.

Using the property $a^{-n} = \frac{1}{a^n}$, we rewrite $7^{-21}$ as $\frac{1}{7^{21}}$.

The expression now becomes $\frac{1}{7^{21}} \cdot 49 \div \frac{1}{36}$.

Finally, we simplify the expression by dividing 49 by 1 and multiplying by 36:

$\frac{1}{7^{21}} \cdot 49 \div \frac{1}{36} = \frac{49}{1} \cdot \frac{36}{7^{21}} = \frac{49 \cdot 36}{7^{21}} = \frac{1764}{7^{21}}$.

So the answer is $\frac{1764}{7^{21}}$.